?ACTIVATION OF FULLER’S EARTH OF D.G. KHAN WITH SULPHURIC ACID - RAFIQUE, MUHAMMAD; YUSAF, MUHAMMAD (Biological Sciences - PJSIR, 1996)
A huge deposit of fuller’s earth essentially montmorillonitic hasbeen identified in D.G. Khan. Aninvestigation on its activation with sulphuric acid was made to make it suitable for cleansing and decolourising edible oils. However, special attention was paid to the comprehensive study of (i) concentration of acid (ii) time of activation and (iii) solid contents of the slurry, for activating the clay to a maximum possible degree so as to make it commercially acceptable.